PEMBACAAN KRITIK SASTRA FEMINIS TERHADAP BEBERAPA NOVEL INDONESIA MODERN - -, Wiyatmi (Diksi, 2008)
This article is about a study describing several writers' perspectivestoward the phenomenon of polygamy based on some novels of theirs and theideology of feminism serving as the background of the perspectives. The novelsstudied are Fira Basuki's Biru, Abidah Al-Khalieqy's Geni Jora and PerempuanBerkalung Surban, and Dewi Sartika's Dadaisme.The result of the study indicates the following. (1) There are three patternsof polygamy in the novels. The polygamy in Al-Khalieqy's Geni Jora and Sartika'sDadaisme is conducted openly with the first wife's permission, her inability tohave a baby being the cause, and both wives have good mutual relationship. Thepolygamy in Al-Khalieqy's Perempuan Berkalung Surban is also conductedopenly but with the first wife forced to give permission, the husband not living inharmony with the first wife and having a love affair resulting in the other woman'spregnancy being the cause, and the wives do not have good mutual relationship.The polygamy in Fira Basuki's Biru is hidden polygamy, that is, without the firstwife's permission, with her relationship with the second wife not being good andthat with her husband not having been good, either, causing him to commit theadultery. (2) Based on the novels, the writers' perspectives toward polygamy are asfollows. Abidah Al-Khalieqy's views polygamy as an emergency and it can beconducted with some requirements being met, among which are economicalcondition and a sense of justice, which are to be seriously considered. If thehusband cannot fulfil the requirements, disharmonious relationship will occur,resulting in divorce. Fira Basuki tends to reject polygamy, viewing the husbandconcerned as doing some injustice. The possible resulting hate in the first wifetoward her husband and the second wife may result in conflict and divorce. DewiSartika allows polygamy, depicting characters who can love more than one person(and consequently commit adultery). (3) There are two streams of feminismserving as the background of the writers' perspectives: radical feminism, reflectedin the works of Al-Khalieqy and Fira Basuki, and liberal feminism, reflected in thework of Dewi Sartika. Radical feminism views polygamy as a form of maledomination over females that results in family problems. Liberal feminism tendsto allow polygamy as a form of patriarchal domination; those committingpolygamy do not always have problems resulting from it and polygamy can be asolution for the problem of not being able to have a child from the first wife.Keywords: polygamy, female writers, feminism